O SUS e a saúde da pessoa idosa: perspectiva na estratégia Saúde da Família na Atenção Básica - Sampaio, Tales Coelho (2013)
Population aging occurs in a globalized manner. It is an unprecedented phenomenon. As societies grow old, they give birth to health problems that challenge health systems, particularly the „SUS‟ (Unified Health System), in the Brazilian case. This is a descriptive study having both quantitative and qualitative focus. The research had as its general objective the attention given to the aged person in the Family-Heealth Strategy (ESF) at the community of „Dendê‟ in Fortaleza and the following specific goals: to identify the socioeconomic and demographic profiles, as well as the profile of the health situation of the aged population at the „Dendê‟ community; to apprehend the perception of the aged themselves regarding the attention given to them by the „ESF‟ of the „Mattos Dourado‟ Family Health Center; to characterize the health professionals and to check whether they are duly qualified to give healthcare assistance to the aged and suggest strategies and/or actions aiming at an integral and integrated to the health of the old person. The study was carried out at two locations: at the community of „Dendê‟ and at the „Mattos Dourado‟ Family Health Center, located at „Edson Queiroz‟ neighborhood. During the quantitative phase, questionnaires were used as collecting instruments for the aged and for the health professionals. With respect to the aged, 99 residents of the „Dendê‟ Community were researched and, as to health professionals, four Nurses and three Medical Doctors answered the questionnaire. The corresponding data were analized by way of the „Epi-Info Version 6.0‟. During the quantitative phase, the „In-Depth Interview‟ technique for data collection was conducted, and eight aged persons were interviewed as well as the focal group with the participation of six community health agents. The data were analized by way of the „In-Depth Hermeneutics‟ method advocated by Thompson (1995). The „Dendê Community‟ aged persons live in homes with precarious infrastructure and no basic sanitation whatsoever. They come from the countryside (69.7%), and are at an average age of 69.7 years old. The majority of them are women (60.6%), married (47.4%), of dusky complexion (84.8%), catholics (63.6%), retired or pensioners (82.8%), with very low income, having as their family income one or two minimum monthly wages (67.6%) and a low level of education (76.7%). They display high physical morbidity, chiefly related to (DCNT) ‟Cronic Non-Communicable Diseases‟ and their risk factors, andself-evaluate their own health conditions from middling to poor (72.4%). The oldest individuals have the perception that the health services rendered by the (PSF) „Family-Health Program‟ have been rather inefficient, since even being satisfied (65.6%), and admitting that the referred to health services have improved the quality of their lives (70.9%), they would leave the „Family-Health Center‟ or their health professional if that were easy for them to do (41.4%). The data analysis suggests that the dissatisfaction regarding the „PSF‟ results from the access hurdles encountered to get medical appointments, the lack of longitudinal follow-up medical monitoring and the lack of comprehensive attention needed by the aged. In relation to the attention that is rendered to the aged, we can come to the conclusion that it is not adequate, since it does not meet their needs. The way to solve those problems points toward the strengthening of the „ESF‟. To achieve such and endeavor, it is essential to invest in infrastructure and professional qualification, by organizing complete and multiprofessional teams. The health of the aged has priority, as a challenge that involves political decisions and awareness on the part of the society regarding care, respect and solidarity for their old citizens.